Ecosystem service management and spatial prioritisation in a multifunctional landscape in the Bay of Plenty, New Zealand. Issue 3 (2nd July 2020) - Powers, Breanna F.; Ausseil, Anne-Gaelle; Perry, George L. W.
ABSTRACT: Sustaining ecosystem services (ES) is a key interest in the management of land use in multifunctional landscapes (i.e. ES that support ecosystem function and sustain human livelihoods). In making land management decisions, it is important to understand the relationships and spatial distributions of multiple ES, and the synergies and trade-offs between them. We analysed nine ES in a catchment in the Bay of Plenty region, New Zealand, to identify areas in the catchment are high (hotspots) and low (coldspots) in supplying multiple ES, the relationships among ES, and where ES trade-offs and synergies occur. We found ES hotspots occurred mainly in indigenous forest. Synergies occurred among provisioning services (milk and meat) and dis-service nitrogen leaching as well as synergies with carbon sequestration and wood supply. Trade-offs occurred between regulating services and a supporting service. We identified ES bundles (services that occur repeatedly together) of provisioning services and those associated with exotic forest. Spatial concurrences and relationships of different ES provide a way to optimise the supply of multiple ES. These results may be used to guide landscape management whereby spatial prioritisation can be used to conserve areas of high ES supply or bundles of ES.